Patient characteristics and statin discontinuation-related factors during treatment of hypercholesterolemia: an observational non-interventional study in patients with statin discontinuation (STAY study) - Lale Tokgözoğlu; Ramazan Özdemir; Rojhat Altındağ; Ceyhun Ceyhan; Ekrem Yeter; Cihan Öztürk; Fahri Bayram; Tuncay Delibaşı; Muzaffer Değertekin; Mustafa Hakan Dinçkal; Ibrahim Keleş; Ali Serdar Fak; et al. (KARE Publishing, 2016)
Objective: The purpose of this study was to identify patient characteristics and statin discontinuation-related factors in patients with hypercholesterolemia. Methods: A total of 532 patients (age mean+-SD: 57.4+-11.5 years; 52.4% women, 47.6% men) with hypercholesterolemia and statin discontinuation were included in this national cross-sectional noninterventional observational study. Data on socio-demographic characteristics of patients, cardiovascular risk factors, past treatment with and discontinuation of statin treatment were collected in one visit. Results: Mean+-SD duration of hypercholesterolemia was 4.9+-4.2 years at time of discontinuation of statin treatment. Statin treatment was initiated by cardiologists in the majority of cases (55.8%), whereas discontinuation of statin treatment was decided by patients in the majority of cases (73.7%), with patients with higher (at least secondary education, 80.4%) more likely than those with lower (only primary education, 69.7%) to decide to discontinue treatment (p=0.022). Negative information about statin treatment disseminated by TV programs-mostly regarding coverage of hepatic (38.0%), renal (33.8%), and muscular (32.9%) side effects (32.9%)-was the most common reason for treatment discontinuation. Conclusion: The decision to discontinue statin treatment was made at the patient's discretion in 74% of cases, with higher likelihood of patients with higher educational status deciding to discontinue treatment and switch to non-drug lipid-lowering alternatives. Cardiologists were the physicians most frequently responsible for the initiation of the statin treatment; coverage of several non-lifethreatening statin side effects by TV programs and patients' lack of information regarding high cholesterol and related risks were the leading factors predisposing to treatment discontinuation.